Does methylene blue help in the early identification of the recurrent laryngeal nerve? - Chhetri, Sujan Singh; KC, Toran; Bista, Meera; Mahato, Nayan Bahadur (Journal of Kathmandu Medical College, 2018)
Background: Identification of recurrent laryngeal nerve is of utmost importance during thyroid surgery. Different anatomical landmarks have been used to recognize and preserve the nerve. Injury may lead to vocal cord paralysis. Different adjuvant methods have been used to aid in the identification of the nerve. Objective: To determine whether methylene blue smear helps to identify the recurrent laryngeal nerve safely and efficiently. Methodology: Observational cross sectional study done in 30 patients who underwent different thyroidectomies within a duration of one year. Recurrent laryngeal nerve identified using methylene blue smear and compared with the conventional visualization techniques exercising different known anatomical landmarks. The duration and ease of identification of the nerve was noted and graded. Results: Total of 39 recurrent laryngeal nerves were identified from 28 females and two males. The duration and the ease of dissection of the nerve was inconstant. Earliest time for recognition of the nerve was one and half minutes while the slowest time was 12 minutes. Conclusion: No matter what techniques are used, visual identification and verification of the recurrent laryngeal nerve is of paramount importance. No techniques demonstrated added advantage to one another.